Estudo da viabilidade do uso do resíduo fosfogesso como material de construção - Mariana Moreira Cavalcanti Canut (2006)
The recycling of the phosphogypsum waste, generated in fertilizer production through the benefaction of the phosphatic rock, is very important as much from a social-economic point of view as regarding environmental preservation. It is an abundant waste witch use could minimize, or even extinguish, the running of natural gypsum mines. Gypsum materials aare very utilized in the civil construction. Its primary application are: execution of the wall covering; cement manufacture and production of many artifacts (e.g. boards, bricks, frames, partitions). The phosphogypsum used in replacement of the efficient natural gypsium indicates an enormous viability and importance, since it associates a material highly consumed by civil construction industry and a waste, produced in large amounts that doesn' t have any adequate final destination in agreement with the demands of the environmental legislation in force. The present project purposes to study and analyze the technical viability, with some economic connotations, of full or partial replacement of the natural gypsum, by the phosphogypsum in the production of materials to be used in the civil construction. In order to accomplish that, tests of physical and chemical characterization of the material have been executed, as well as mechanical tests with phosphogypsum and gypsum usually used in construction. Through the presented results it was possible to observe that the use of phosphogypsum waste as a construction material in replacement of the natural gypsum is extremely viable.